DIALOG AGAMA DAN BUDAYA; MENANGKAL GERAKAN RADIKALISME DI TAPANULI - Puji Kurniawan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Radicalization can be seen through various media. Some are triggered by religio-political problems, inter-religious interaction and injustice. Religion is often referred to as the dominant factor in committing acts of violence. Religion which initially had a peaceful mission was reduced by acts of violence that were contrary to its teachings. Radicalism or fundamentalism is an interesting religious, social and political issue to study. Radical actions are not only labeled with adherents of Islam, but also followers of other religions such as Christianity, Judaism, Hinduism and Buddhism. Based on historical search, the phenomenon of radicalism is a symptom that occurs in almost all religions.